Condom Use and its Associated Factors Among Iranian Youth: Results From a Population-Based Study - Samira Hosseini Hooshyar; Mohammad Karamouzian; Ali Mirzazadeh; Ali Akbar Haghdoost; Hamid Sharifi; Mostafa Shokoohi (Kerman University of Medical Sciences, 2018)
Background Given the young structure of Iran's population and the fact that extramarital sexual relationships are both prohibited by legislation and shunned by society and religion, examining condom use practices among Iranian youth is highly important. The aim of this study was to explore condom use and its correlates among Iranian young adults. Methods In a sample of 3,045 individuals aged 19-29 who were recruited from a nation-wide study, we analyzed data from 633 participants who reported a history of extramarital sex. Subjects were asked about their condom use practices during their last penetrative sex. Data were collected through a self-administered questionnaire where the respondents completed the survey on their own and passed it to trained gender-matched interviewers. Multivariable regression models were constructed to report adjusted odds ratios (AOR) along with 95% CI. Results Of the 633 participants, 222 (35.1%) reported condom use at last sex. Men reported significantly higher condom use than women (38.5% vs. 25.7%). Having a stable job (AOR = 1.86, 95% CI: 1.01, 3.43), higher knowledge of condom use (AOR = 1.57, 95% CI: 1.03, 2.37) and sexual transmission of HIV (AOR = 1.83, 95% CI: 1.18, 2.85) were positively associated with condom use at last sex. Conversely, experience of sex under the influence of substances (AOR = 0.66, 95% CI: 0.45, 0.94) was significantly associated with reduced odds of condom use at last sex. Conclusion This study shows that only one out of every three young adults reported using condoms at last sex. While educational programs are helpful, multi-sectoral approaches (eg, individual-, community-, and structural-level interventions) are required to change sexual behaviours towards safe sex practices and reinforce negotiating condom use among youth.